Characterization of Celosia argentea Linn. germplasm using ISSR markers - Odunayo Joseph OLAWUYI; Haneefah Lola MISBAHUDEEN; Oluwagbade Joseph ODIMAYO; Adedayo Omotayo FANEYE; Olumayowa Mary OLOWE; Akinlolu Olalekan AKANMU (Studia Universitatis Babeș-Bolyai. Biologia)
Celosia argentea is an annual leafy vegetable popularly known for its dietary and medicinal values. Hence, it is important to preserve and further improve this vegetable to enhance its numerous benefits. This study therefore investigated the genetic variability among different genotypes of C. argentea using ISSR primers. A total of 15 C. argentea genotypes were sourced from National Centre for Genetic Resources and Biotechnology (NACGRAB) in Ibadan, Nigeria and 10 genotypes sourced from different markets. The open field experiment was set up in a completely randomized design. Seeds of each cultivar were grown, and seedlings transplanted. Fresh young apical leaves were harvested. DNA was extracted from young frozen apical leaves. Six ISSR primers were optimized and used in PCR with a touch-down procedure in a thermocycler. Agarose gel electrophoresis was performed, and bands were visualized. Molecular data was analyzed for total gene diversity, while morphological data was analyzed using ANOVA. The genotypes of NGB recorded the highest mean performance for plant height, leaf biomass and seed weight, while the A00 genotypes were observed to have higher values of leaf length, leaf area and root biomass. The principal component analysis showed that the first component accounted for 42% of the total variation. The correlation matrix for growth, agronomic and yield characters show highly significant positive relationship among the growth characters at P<0.05. Primer UBC-866(CTC)6 was highly polymorphic. Genotype A005 performed best for growth characters while NGB00182 performed best for yield characters. Genetic assessment and improvements in C. argenta germplasm play key role in future studies and improvements of vegetable crop.